The Use of Peer Evaluation to Improve Writing Ability Students of SMP Negeri 1 Rambah Hilir - Neni Triana; Yusrida Yusrida (Universitas Muhammadiyah Kalimantan Timur, 2022)
The main purpose of this research is to find out of the improving students writing ability using peer evaluation at SMP Negeri 1 Rambah Hilir. The design of this research is classroom action research the data were collected by distributing the test to the students of participants. There were two techniques in collecting the data. They were pre-test and post-test. Pre-test has been conducted to find the ability of students’ writing ability before teaching by using Peer Evaluation. After giving pre-test, the treatment has been done by using Peer Evaluation. The participants of this research were the eighth grade students of SMP Negeri 1 Rambah Hilir. The total population is 40 students of the tenth grade. This research used a cluster sampling technique to get samples. The total . In this research, the data were collected by distributing the test to the students of participants. There were two techniques in collecting the data. They were pre-test and post-test. The result showed that there are increasing average scores of students from 55.96 (Pre-Test), to 61.00 (Post-Test 1), and 70.58 (Post-Test 2).It means that using Peer Evaluation in teaching writing is effective to improve students’ ability in writing a recount text